Indiaas Look East Policy: Challenges and Opportunities Ahead (Global Journal of Human-Social Science, 2012)
Prior to 1991 India almost did not look to its neighbouring Eastern countries Rather it maintained a very close relationship with the Western and Middle East countries Because firstly asa colonial habitants of the British India the entire mindset of the people of India was dominated by the Socio-economic philosophy of the western countries Secondly India was tied up with the then USSR during the Cold War period Thirdly India had to import most of the imported goods from defence equipments to petroleum products or crude oil and natural gas etc from the Western and Middle East countries With the collapse of the Soviet Union the Cold War period came to an end when most of the nations accepted the new era of Globalisation Liberalisation and Privatization in their economy as well as other socio-cultural fields The nations have realized that the means to making wealth is by developing of international trade and encouragement of foreign investments etc The South East Asian countries have also experienced with the New Economic Reform Policies as a result there have been rapid economic development and growth in South East Asian countries Thus with the introduction of the New Economic Policy 1991 India opened its door to the South East Asian countries for trade and other socio-economic activities
Keywords: East Policy; Challenges and Opportunities